Interactive algorithm for generating accurate as-built plans by building owners - Brandão, F. (2021)
Mass Customization systems in architecture have yet to adequately address the problem of capturing physical context, a fundamental aspect of dealing with building renovation, which has limited their scope of application. Previous research has demonstrated that existing methods of capturing as-built plans of rooms by non-expert users do not produce sufficiently accurate results for digital fabrication. The present paper reports on research into the development of an algorithm for semi-automated survey of convex or non-convex rooms by building owners. The improved workflow is tested by expert and non-expert users in a to-be renovated building and the results are compared with existing methods of survey.